Effect of Policy Change to Require Laboratory Reporting With Pregnancy Indicated for Syphilis and Hepatitis B Virus Infection, New York City, January 2013–June 2018. (July 2020) - Liao, Tim S.; Hashmi, Ariba; Lazaroff, Julie; Hennessy, Robin R.; Sanders Kim, Afua; Evans Lloyd, Pamela; Rosen, Jennifer B.
Objectives: We evaluated the impact of a 2014 New York City health code change requiring laboratories to indicate if a patient is pregnant or probably pregnant in the electronic laboratory report (ELR) when reporting syphilis and hepatitis B virus (HBV) cases to the New York City Department of Health and Mental Hygiene (DOHMH). Methods: We calculated the number of pregnant persons with syphilis or HBV infection reported to DOHMH from January 1, 2013, through June 30, 2018. We compared the proportion in which the first report to DOHMH was an ELR with pregnancy indicated before and after the policy change. We calculated time between first ELR with pregnancy indicated and subsequent reporting by a method other than ELR and the proportion of cases in which ELR with pregnancy indicated was the only report source. Results: A total of 552 new syphilis and 8414 HBV-infected cases were reported to DOHMH. From January 2013–June 2014 (pre-change) to January 2017–June 2018 (post-change), the proportion of cases in which ELR with pregnancy indicated was the first report to DOHMH increased significantly (14.7% [23/156] to 46.2% [80/173] for syphilis; 8.0% [200/2498] to 45.3% [851/1879] for HBV infection [ P < .001]). Median time between first ELR with pregnancy indicated and subsequent reporting by a method other than ELR was 9.0 days for syphilis and 51.0 days for HBV infection. ELR with pregnancy indicated was the only report for 43.1% (238/552) of syphilis cases and 23.4% (1452/6200) of HBV cases during the study period. Conclusion: Including pregnancy status with ELR can increase the ability of public health departments to conduct timely interventions to prevent mother-to-child transmission.